2018
DOI: 10.2196/10351
|View full text |Cite
|
Sign up to set email alerts
|

Participant Recruitment and Retention in Remote eHealth Intervention Trials: Methods and Lessons Learned From a Large Randomized Controlled Trial of Two Web-Based Smoking Interventions

Abstract: BackgroundDespite having many advantages, online eHealth trials are not without challenges—notably, participant recruitment, and outcome data retention. Moreover, publications from these trials rarely provide detailed information on the methods used for recruitment and retention or discuss implications of the methods for future studies.ObjectiveTo address this need for empirical guidance regarding recruitment and outcome data retention planning, we aim to describe the methods and lessons learned from the recru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 55 publications
4
85
0
1
Order By: Relevance
“…Due to scientific ethical codes (voluntary participation), involvement of the employer may be difficult to implement in a research setting. Several EHI studies found that recruitment using social media such as Facebook is more successful than more traditional recruitment strategies such as advertising [ 53 , 54 ]. However, such strategies seem difficult to apply to the population of employees with frequent SA.…”
Section: Discussionmentioning
confidence: 99%
“…Due to scientific ethical codes (voluntary participation), involvement of the employer may be difficult to implement in a research setting. Several EHI studies found that recruitment using social media such as Facebook is more successful than more traditional recruitment strategies such as advertising [ 53 , 54 ]. However, such strategies seem difficult to apply to the population of employees with frequent SA.…”
Section: Discussionmentioning
confidence: 99%
“…Participation was low, which suggests that future research should consider other strategies to facilitate increased uptake. Enhancing participation by providing quotes from previous participants, a study information page, following up with email reminders, including information about the importance of sun protection in skin cancer risk reduction, and using multiple social media recruitment methods (Google, Instagram) may increase uptake ( Treweek et al, 2018 ; Watson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Study promotion and recruitment approaches have been identified as important determinants of successful recruitment [ 39 ]. A combination of web-based and offline strategies has worked well to recruit participants into web-based trials in health research [ 19 , 40 ]. Despite some challenges, such as cost, the potential for misrepresentation, and potentially low recruitment rates [ 11 ], Facebook has proved to be a highly successful web-based recruitment strategy [ 19 , 41 ].…”
Section: Updates and Insightsmentioning
confidence: 99%
“…Previous studies have found a difference in demographics depending on whether participants were recruited on the web or offline [ 19 , 38 , 39 ], but not all studies have identified the same differences. There is some agreement that more females than males come into research through web-based strategies, such as Facebook [ 19 , 42 ], and evidence that more highly educated participants are more likely to be recruited offline [ 19 ].…”
Section: Updates and Insightsmentioning
confidence: 99%
See 1 more Smart Citation